Properties of raw meat and meat curry from spent goat in relation with post-mortem handling conditions - Narayan, Raj (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2013)
The properties of raw meat and meat curry from spent goat meat in relation with post-mortem handling conditions were evaluated. The conditions evaluated were: cooking of meat within 1-2 h post-slaughter (condition 1); deboning meat storage at 25 ± 2 °C for 5-6 h and cooking (condition 2); post-slaughter storage of carcass at room temperature for 5-6 h, then deboning followed by storage of meat at refrigeration temperature for 5-6 h and cooking (condition 3); deboning and storage of meat at 25 ± 2 °C for 10-12 h and cooking (condition 4). Significant difference was observed in pH values in condition 1 (p < 0.01) and moisture content (p < 0.05) of raw meat as compared to the conditions 2, 3 and 4. However, the moisture content of cooked meat was significantly higher (p < 0.05) for conditions 1 and 2 as compared to the conditions 3 and 4. Significant differences were also observed in muscle fiber diameter values of different conditions, that is, the mean values were significantly higher (p < 0.05) for conditions 2 and 4 and significantly lower for condition 1. The mean water holding capacity and cooking yield values were highest in condition 1, followed by conditions 2, 3 and 4. The significant differences was also observed in shear force value of cooked meat chunks, that is, the mean value was significantly higher (p < 0.01) for condition 2 and significantly lower for condition 1. Sensory scores were significantly higher in condition 1 and significantly lower in condition 2. However, sensory scores for condition 4 were almost similar to the condition 1